2019
DOI: 10.3390/ijms20184381
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem-Cell-Derived Cardiomyocytes as Models for Genetic Cardiomyopathies

Abstract: In the last few decades, many pathogenic or likely pathogenic genetic mutations in over hundred different genes have been described for non-ischemic, genetic cardiomyopathies. However, the functional knowledge about most of these mutations is still limited because the generation of adequate animal models is time-consuming and challenging. Therefore, human induced pluripotent stem cells (iPSCs) carrying specific cardiomyopathy-associated mutations are a promising alternative. Since the original discovery that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 496 publications
(253 reference statements)
0
40
0
Order By: Relevance
“…The heart is a complex tissue consisting of multiple cell types, yet the bulk of the volume of the heart is comprised of cardiomyocytes Pinto et al, 2016), which are particularly susceptible to oxygen deprivation given their high metabolic activity. iPSC-derived cardiomyocytes (iPSC-CMs) have been shown to be a useful model for studying genetic effects on various cardiovascular traits and diseases, as well for studying gene regulation (Banovich et al, 2018;Benaglio et al, 2019;Brodehl et al, 2019;Burridge et al, 2016;de la Roche et al, 2019;Ma et al, 2018;McDermott-Roe et al, 2019;Panopoulos et al, 2017;Pavlovic et al, 2018;Ward and Gilad, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The heart is a complex tissue consisting of multiple cell types, yet the bulk of the volume of the heart is comprised of cardiomyocytes Pinto et al, 2016), which are particularly susceptible to oxygen deprivation given their high metabolic activity. iPSC-derived cardiomyocytes (iPSC-CMs) have been shown to be a useful model for studying genetic effects on various cardiovascular traits and diseases, as well for studying gene regulation (Banovich et al, 2018;Benaglio et al, 2019;Brodehl et al, 2019;Burridge et al, 2016;de la Roche et al, 2019;Ma et al, 2018;McDermott-Roe et al, 2019;Panopoulos et al, 2017;Pavlovic et al, 2018;Ward and Gilad, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, they can overcome certain limitations that have been attributed to PSCs, including ESC and iPSC. In contrast to ESC, MSC do not provoke any ethical concerns [12,37,38]. Moreover, pre-clinical studies demonstrated a tumorigenic potential of ESC and iPSC-derived cell products that has not been observed for MSC to date [42][43][44][45].…”
Section: Discussionmentioning
confidence: 98%
“…In vitro generated cardiomyocytes are an important tool for cardiovascular research, as they can be utilized for disease modelling or for the development of drug screening assays to assess the cardiac toxic risk of established or newly synthesized drugs [37][38][39]. Moreover, promising preclinical data suggests the therapeutic potential of generated cardiomyocytes for the treatment of cardiac diseases to overall improve heart regeneration and function [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CRISPR/Cas9 has been zealously received by cell biologists as an attractive tool for SC research [203]. In cardiovascular biology, CRISPR/Cas9 was successfully applied to patient-derived iPSC to target disease-causing mutations of CVDs [204][205][206]. A recent study demonstrated the utility of CRISPR/Cas9 in phenotypic characterization of iPSC-CMs from patients with arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) [207].…”
Section: Genetic Modification Of Pluripotent Stem Cellsmentioning
confidence: 99%